Colloidal nanocrystals for heterogeneous catalysis. (February 2019) - Losch, Pit; Huang, Weixin; Goodman, Emmett D.; Wrasman, Cody J.; Holm, Alexander; Riscoe, Andrew R.; Schwalbe, Jay A.; Cargnello, Matteo
Graphical abstract: Highlights: Colloidal nanocrystals can be prepared with high degree of control in size, shape and composition. Colloidal nanocrystals are used as building blocks to prepare heterogeneous catalysts with uniform nanostructures. Colloidal catalysts are used to derive accurate structure-property relationships in thermal, electro- and photocatalysis. Abstract: Catalytic materials are an essential component of the chemical industry. They find applications in everything from fine chemical manufacturing to greenhouse gas mitigation. They are indispensable for developing a sustainable future. Their development has been continuous, from early trial and error efforts to the first fundamental insights gained through surface science, to modern in-situ characterization and computational predictions. The accumulation of knowledge on the working principles of catalytic surfaces allowed designing and producing better systems with improved performance. Even though tremendous progress has been made thanks to surface science techniques, these studies are usually performed under ultra-high vacuum and are therefore limited in their applicability to more relevant industrial conditions. The control over size, shape and composition in colloidal nanocrystals makes them formidable precursors for model heterogeneous catalysts. These model systems enable linking the insights from surface science studies via in-situ and operando studies to realistic catalytic reaction conditions. In this review, colloidal nanocrystals are presented as powerful building blocks for catalytic materials in the quest for fundamental understanding. A review of the principal methods to produce colloidal nanocrystals with a high level of control is reported, complemented by procedures for how to prepare active catalysts from these particles. Examples and guidelines for the catalytic applications of these materials revolve around the three guiding objectives in catalysis science: activity, selectivity and stability. This work will be limited to examples of this colloidal approach in the areas of thermal, electro- and photocatalysis. The exposed approaches can be used and extended to many other areas of catalysis science, thus providing a new avenue to explore fundamentals and applications of catalytic materials.